ANDROGEN RECEPTOR EXPRESSION IN ENDOMETRIAL CARCINOMA AND ITS CORRELATION WITH ESTROGEN RECEPTOR AND PROGESTERONE RECEPTOR AND CLINICOPATHOLOGICAL FINDINGS - Nisar, Maryam; Mushtaq, Sajid; Hassan, Usman; Akhtar, Noreen; Azma, Muhammad (Journal of Ayub Medical College Abbottabad, 2020)
Background: The objective of the study is to analyze the expression of androgen, estrogen and progesterone receptor in different types of endometrial carcinomas and to correlate the androgen receptor expression with estrogen and progesterone receptor and the clinicopathological parameters like lymphovascular invasion, grade of the tumour, size of tumour and extent of myometrial invasion. Methods: It is a cross-sectional analytical study design with a simple random sample of a total of 54 cases of different types of endometrial carcinomas from the year 2017. Immunohistochemical stains androgen receptor, estrogen receptor, and Progesterone receptor were applied in all the cases. The Pearson Chi-square test of independence was applied to measure association and P-value is calculated to check the significance of the results. Results: Androgen receptor expression was observed in 73% of low-grade endometrioid carcinomas, 62.5% of high-grade endometrioid carcinomas, 62% of serous, 20% of clear cell and 18% of carcinosarcomas, respectively. Androgen positive tumours were also positive for estrogen and progesterone in most of the cases, except 3 serous carcinomas and one low-grade endometrioid carcinoma. However, no significant relation was observed between androgen expression and prognostic parameters like the lymphovascular invasion, size of the tumour and myometrial invasion. Conclusion: Maximum expression of androgen receptor was observed in endometrioid and serous carcinomas, while carcinosarcomas and clear cell carcinomas showed minimum expression with no significant correlation between androgen receptor expression and clinicopathological parameters. Keywords: Endometrioid carcinoma; Serous carcinoma; Clear cell carcinoma; Androgen receptor; Immunohistochemical stains